2023
DOI: 10.3390/cancers15153757
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted MRI for Treatment Response Assessment in Osteoblastic Metastases—A Repeatability Study

Abstract: The apparent diffusion coefficient (ADC) is a candidate marker of treatment response in osteoblastic metastases that are not evaluable by morphologic imaging. However, it is unclear whether the ADC meets the basic requirement for reliable treatment response evaluation, namely a low variance of repeated measurements in relation to the differences found between viable and nonviable metastases. The present study addresses this question by analyzing repeated in vivo ADCmedian measurements of 65 osteoblastic metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The DWI sequence has proven effective for distinguishing bone metastases from both solid tumors and hematological malignancies (Pasoglou et al 2015 ; Dimopoulos et al 2015 ; Hottat et al 2024 ). DWI also allows for quantifying lesion cellularity through ADC maps and numerous studies have demonstrated its value in bone metastases (Costelloe et al 2021 ; Eveslage et al 2023 ; Perez-Lopez et al 2018 ). In our study, the ADCmin value for metastatic bone lesions was significantly lower than that for non-metastatic lesions (618 ± 204 × 10 −6 mm 2 /s vs. 1077 ± 325 × 10 −6 mm 2 /s, P = 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…The DWI sequence has proven effective for distinguishing bone metastases from both solid tumors and hematological malignancies (Pasoglou et al 2015 ; Dimopoulos et al 2015 ; Hottat et al 2024 ). DWI also allows for quantifying lesion cellularity through ADC maps and numerous studies have demonstrated its value in bone metastases (Costelloe et al 2021 ; Eveslage et al 2023 ; Perez-Lopez et al 2018 ). In our study, the ADCmin value for metastatic bone lesions was significantly lower than that for non-metastatic lesions (618 ± 204 × 10 −6 mm 2 /s vs. 1077 ± 325 × 10 −6 mm 2 /s, P = 0.004).…”
Section: Discussionmentioning
confidence: 99%